2013
DOI: 10.2209/tdcpublication.54.215
|View full text |Cite
|
Sign up to set email alerts
|

Association between Feeding Methods and Sucking Habits: A Cross-sectional Study of Infants in Their First 18 Months of Life

Abstract: The aim of this study is to investigate infant feeding patterns and to analyze the influence of breast-feeding methods on the prevalence of non-nutritive sucking habits in a sample of Japanese infants. A random sample of 353 mothers of infants of 18 months of age was interviewed at a public health facility in "K" city. The prevalence and duration of infant feeding patterns categorized as breast-feeding, partial breast-feeding, and bottlefeeding, were determined. The outcome investigated was the prevalence of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
7
1
3
Order By: Relevance
“…We found strong relationship between pacifer usage and ECC (p=0.022). In parallel, World Health Organization (WHO) and United Nations Children Fund (UNICEF) are also recommending against the use of pacifiers since pacifier usage shortens breasfeeding duration and reported to be a factor for malocclusion of teeth [19]. In addition, many studies show strong evidence between pacifier usage and disease posession such as otitis media [20].…”
Section: Discussionmentioning
confidence: 99%
“…We found strong relationship between pacifer usage and ECC (p=0.022). In parallel, World Health Organization (WHO) and United Nations Children Fund (UNICEF) are also recommending against the use of pacifiers since pacifier usage shortens breasfeeding duration and reported to be a factor for malocclusion of teeth [19]. In addition, many studies show strong evidence between pacifier usage and disease posession such as otitis media [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of different designs, systematic review, clinical trial, longitudinal and cross-sectional studies have associated non-nutritive suckling habits with early weaning, malocclusions and socioeconomic factors in children (12)(13)(14)(15)(16)(17)(18)(19). One case-control study observed that children aged 3 to 6 years who were born prematurely had a 3.3-fold greater chance of developing non-nutritive sucking habits (20).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it should be highlighted that the use of babybottle is associated with the consumption of sweetened liquids at high frequency and during sleeping periods, predisposing the infant to the appearance of caries lesions, a situation that must be taken into account for the adoption of preventive measures against dental caries disease. The use of pacifier involves emotional and psychological aspects, also complementing the need for suction from the interruption of breastfeeding, which can contribute to the persistence of the nonnutritive sucking habit [29]. The results of this study show a high prevalence of babybottle (45%) and pacifier use (25%), and as a result, a high prevalence of malocclusions -57.9%.…”
Section: Discussionmentioning
confidence: 70%